2017
DOI: 10.1039/c7lc00545h
|View full text |Cite
|
Sign up to set email alerts
|

Design and modeling of electrode networks for code-division multiplexed resistive pulse sensing in microfluidic devices

Abstract: A typical microfluidic device sorts, captures or fractionates sample constituents by exposing them to discriminating microenvironments. Direct electronic acquisition of such manipulation by a network of integrated sensors can provide a fast, integrated readout, replacing otherwise required microscopy. We have recently introduced a sensor technology, Microfluidic CODES, which allows us to multiplex resistive pulse sensors on a microfluidic device. Microfluidic CODES employs a network of micromachined coplanar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Matched filters are generally used to identify a known signal or template in an unknown signal. The matched filter can improve noise rejection and extract features out of a noisy signal Matched filters have been extensively used for the detection of blood vessels, ECG peaks, seismic events, moving targets, cracks, SONAR, and microfluidic cells [44][45][46][47][48][49][50][51]. It is similar to the convolution of an unknown signal with a conjugated time-reversed version of the template.…”
Section: Wheeze Detection Using Matched Filtermentioning
confidence: 99%
“…Matched filters are generally used to identify a known signal or template in an unknown signal. The matched filter can improve noise rejection and extract features out of a noisy signal Matched filters have been extensively used for the detection of blood vessels, ECG peaks, seismic events, moving targets, cracks, SONAR, and microfluidic cells [44][45][46][47][48][49][50][51]. It is similar to the convolution of an unknown signal with a conjugated time-reversed version of the template.…”
Section: Wheeze Detection Using Matched Filtermentioning
confidence: 99%
“…Our sensing strategy is based on the Microfluidic CODES scheme, which uses micromachined electrode patterns to multiplex spatiotemporal cell data across a microfluidic device. [30][31][32] In our device, a three-electrode Coulter counter was shaped to form distinct electrode patterns (i.e., sensors) at six different nodes to monitor cell passage between microfluidic chambers. Each sensor is composed of an array of 5 μm-wide finger electrodes separated by 5 μm gaps and produces a specific 31-bit digital code, which was implemented by an interdigitated arrangement of three electrodes: two sensing electrodes to set the bit polarity (positive for "1" and negative for "0") and one common electrode meandering in between to excite the sensor network ( Figure 1d).…”
Section: Device Design and Operationmentioning
confidence: 99%
“…In addition, we designed sensor codes to be mutually orthogonal (Gold sequences), [33,34] and therefore, we could 1 by the same or different sensors (Table 1.1). [30,32] Moreover, in the case of cell debris or aggregates, the electrical signal generated by sensors do not match any of the templates constructed based on single cell signals and therefore, these data are discarded and do not affect the assay performance. Figure 3.…”
Section: Device Design and Operationmentioning
confidence: 99%
“…To address the signal overlapping issue, Liu et al demonstrated a microfluidic CODES technology based on the code division multiple access (CDMA) principle to simultaneously resolve signals from a combined waveform. 102,103 The CDMA technology, widely used in telecommunications, achieves signal multiplexing by modulating signals from individual channels with different orthogonal digital spreading codes; individual signals can be recovered by crosscorrelating the multiplexed signal with standard templates, i.e., the measured analog square pulse signals representing each digital spreading code. The sensing principle of the microfluidic CODES method is shown in Fig.…”
Section: Codes Multiplexingmentioning
confidence: 99%